2016
DOI: 10.1080/13696998.2016.1227829
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns, complications, and direct medical costs associated with ankylosing spondylitis in Chinese urban patients: a retrospective claims dataset analysis

Abstract: Biologics were not commonly used for AS in Chinese patients likely due to their high cost. Future studies are needed to confirm the potential long-term clinical benefits associated biologic treatment for AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The association between patient demographics, baseline comorbidities of interest, baseline medications received, and the subsequent initiation of a bDMARD in the 12 months after diagnosis of AS was assessed using a multivariable logistic regression model. The selection of covariates was based on clinical importance and a literature review [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The association between patient demographics, baseline comorbidities of interest, baseline medications received, and the subsequent initiation of a bDMARD in the 12 months after diagnosis of AS was assessed using a multivariable logistic regression model. The selection of covariates was based on clinical importance and a literature review [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…For AxSpA, NSAIDs are often the first-line treatment, and biologics are the step-up treatment for patients who have inadequate response to NSAIDs [27]. However, the cost difference between NSAIDs and biologics is very large [51]. Patients who have inadequate response to NSAIDs but cannot afford biologics often experience significant pain and impairment in QoL [52].…”
Section: Discussionmentioning
confidence: 99%
“…Previous retrospective studies have predominantly focused on treatment patterns and costs of TNFis. 31,32 Therefore, there is a need for more studies evaluating the real-world health care costs and utilization associated with newer biologic treatments for RESULTS: A total of 791 patients with AS who were newly initiating a biologic were categorized as switchers (15.4%), nonswitchers (53.1%), and discontinuers (31.5%). Switchers and discontinuers had higher all-cause health care utilization than nonswitchers during the 1-year follow-up period.…”
Section: What This Study Addsmentioning
confidence: 99%
“…A previous study using a claims database in China reported that patients with AS receiving biologics have the highest direct medical costs compared with those on other conventional therapies. 32 To account for potential confounding of baseline health status, we adjusted for baseline covariates that may represent a patient's need for health care services as a proxy for health status or predictors of future health care utilization (e.g., age, sex, and comorbidities).…”
Section: Limitationsmentioning
confidence: 99%